Development of nanocatalysts via co-precipitation cum modified stöber method and application to methane decomposition / Muhammed Ashik.U.P - Muhammed Ashik, U.P (2016)
Nanoparticle formation from their respective precursors through bottom-up method is a very fascinating practice in nanotechnology. This research contribution discusses two promising bottom-up methods: i) controlled precipitation of Ni, Fe, and Co nanoparticles and reinforcement with silicate through modified Stöber method, and ii) chemical vapor deposition of nanocarbon from methane. Thermocatalytic decomposition of methane is a fully green single step technology for producing hydrogen and nanocarbon. In spite of having great success in the laboratory scale production, industrial thermocatalytic decomposition of methane for greenhouse gas free hydrogen production is still in its infancy. However, deactivation of catalyst is the prime drawback found in thermocatalytic decomposition of methane. In this research contribution, n-NiO/SiO2, n-FeO/SiO2, and n-CoO/SiO2 nano-structured catalysts were prepared by co-precipitation cum modified Stöber method and used for thermocatalytic decomposition of methane to produce hydrogen and carbon nanotubes. Our experimental results reveal that the metal oxide particles were formed as single crystal nanoparticles upon the addition of silicate and exhibited catalytic activity promoting features, such as lower particle size and higher surface area and porosity. Temperature programmed methane decomposition from 200 to 900 °C were conducted in a fixed bed pilot plant as preliminary catalytic examination and further isothermal analysis were performed in between 475 and 700 °C. Production of hydrogen at each experimented temperature and corresponding carbon yield were measured. Among the three catalysts inspected, n-NiO/SiO2 found as the most efficient one for thermocatalytic methane decomposition and exhibited methane transformation activity more than 300 min, without a significant deactivation at temperature range from 475 to 600 °C, designating the resistance capability of analyzed nano-structured catalyst irrespective of many reported catalysts. n-NiO/SiO2 produced an enormous carbon yield of ~5000% at 600 °C within 5 h of experiment. While, the rapid deactivation of the n- iv FeO/SiO2 and n-CoO/SiO2 catalysts were attributed to the particle agglomeration and irregular formation of nanocarbon due to the metal fragmentation. Most efficient n-NiO/SiO2 catalyst was selected for further studies. Methane decomposition kinetics over n-NiO/SiO2 catalyst were studied by considering thermodynamic deposition of carbon at a temperature range of 550 to 650 °C and methane partial pressure from 0.2 atm to 0.8 atm. The findings concluded that the enhancement occurred with carbon formation rate when increasing the methane partial pressure, which is very much evident at higher temperature such as 650 °C. The effects of methane partial pressure and reaction temperature on the specific molar carbon formation rate were examined. The calculated reaction order and activation energy were found to be 1.40 and 60.9 kJ mol-1, respectively. The governance of porosity and methane decomposition activity sustainability of n-NiO/SiO2 catalyst by changing synthesis parameters such as nickel/silicate ratio, C18TMS/TEOS ratio and different solvents were also conducted. Physical and chemical characteristics of produced nano-catalysts were performed by N2 adsorption-desorption measurement (BET), X-ray diffraction (XRD), transmission electron microscopy (TEM), field-emission scanning electron microscopy - Energy-dispersive X-ray spectroscopy (FESEM-EDX), and hydrogen-temperature programmed reduction (H2-TPR). Produced nanocarbons were inspected with TEM, FESEM, and XRD.